Comparing the Effectiveness of Local Heat and Foot Massage in Reducing the Pain Caused by Heel Blood Sampling in Neonates - Reyhaneh Barzegari; Seyed Hamid Seyed Bagheri; Hassan Khodadadi; Tabandeh Sadeghi (Iranian Journal of Neonatology)
Background: Given the inevitability of heel blood sampling for thyroid testing in neonates, this study aimed to compare the effectiveness of local heat and foot massage in reducing pain caused by the procedure. Methods: This experimental study was conducted on neonates admitted to a healthcare center for thyroid testing in Rafsanjan, southeast Iran. Neonates were selected through convenience sampling and randomly assigned to one of three groups: foot massage, local heat, or control. In the foot massage group, the outer part of the neonates' heel was massaged for three minutes before blood collection. In the local heat group, the neonates’ heel was heated to 40 °C for 3 minutes using a hair dryer before blood sampling. No specific intervention was performed in the control group. The Neonatal Infant Pain Scale (NIPS) was used to measure pain intensity. Data were analyzed using SPSS software. Results: Data analysis revealed a statistically significant difference between the mean pain scores in the local heat group and the control group (P<0.001), as well as between the massage group and the control group (P<0.001). However, there was no significant difference in mean pain scores between the massage and local heat groups (P=0.83). Conclusion: The findings suggest that both local heat and foot massage interventions are effective in reducing pain caused by heel blood sampling. Therefore, either method can be used for pain reduction depending on the neonates’ condition.